Critical review of catalysis-assisted nanofiltration for micropollutants removal: Catalytic coupled nanofiltration system vs catalytic nanofiltration membrane. Issue 9 (3rd May 2023) - Zhu, Tingting; Li, Xin; Zhu, Xuewu; Liu, Bin; Zhu, Junyong; Luo, Jianquan
Abstract: The integration of nanofiltration with catalysis enables high-efficient removal of micropollutants due to its remarkable high selectivity and superior degradation efficacy. Meanwhile, the catalysis-assisted nanofiltration can largely alleviate the issues of inferior low-molecular-weight micropollutants selectivity, membrane fouling and tradeoff limitation. Two different technical routes, catalytic coupled nanofiltration system and catalytic nanofiltration membrane, have been developed based on nanofiltration module and material design for micropollutants separation enhancement. In this review, we first summarize the underlying governing principles of the latest progress of catalysis coupled nanofiltration and catalytic nanofiltration membrane for micropollutants removal. The catalysis and filtration performance of these two routes were initially discussed and compared based on various catalytic oxidation conditions and target substances. We then discussed the corresponding catalytic membrane material innovation and preparation strategies (e.g. coating, bottom-up synthesis, blending, etc.). Finally, we point out the prospects and challenges of catalysis-assisted nanofiltration for micropollutants removal. This review provides directions and guidance for further catalysis-assisted nanofiltration module development and technical industrialization. Graphical abstract: UF0001